Eläimet ja affekti — etymologisia huomioita - Kulonen, Ulla-Maija (Kotikielen Seura, 2006)
Animals and affectivity — etymological observations (englanti)3/2006 (110)Animals and affectivity etymological observationsThe article examines the oldest names for animals in the Finno-Ugrian languages and the etymology of these names, focusing particularly on indications of emotional attitudes, or affectivity, in relation to animal naming.The taboos associated with large animals, especially predators, commonly lead to the entire name being replaced by a periphrastic expression. Names of large animals have therefore been poorly preserved in Finno-Ugrian languages, and only very few of them have been restored to their proto-language form.Typical of the names given to small animals has been the increase in their expressiveness, whereby the names are retained unchanged but there is a considerable amount of phonological variation. At the proto-language level, the names of small animals indicate family similarities typical of expressive words. Indeed, the same phonological mould is shown to be represented by no less than six separate names of small animals reconstructed in the proto-language (conca ~ coca flea, kunc? ~ kuc? parasitic worm, kunc? ~ kuc? ant, l?nc? fly, horsefly, omca insect, beetle, s??c?(-l?) ~ s?c?(-l?) lizard). Many other early names of small animals have become phonologically differentiated from each other in various ways, involving typical means of expressive word formation: variation in vowel use, richness of derivation and the suffix substitution associated with it.The emergence of certain parallels also justifies the Saami word for mouse being combined with the Finno-Ugrian hiiri word family. The Saami word has generally been omitted from the word family on phonological grounds.Ulla-Maija Kulonen